Philosophical concepts relevant to sciences in Indian tradition - Sen, Pranab Kumar (New Delhi: Centre for Studies in Civilizations, 2006)
Contributed research papers.
"Project of History of Indian Science, Philosophy, and Culture."
Includes bibliographical references and index.
Keywords: PHILOSOPHY; SCIENCE-ANCIENT; SCIENCE